2020
DOI: 10.1111/jzs.12368
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the sources of postglacial range expansion in two large European land snails

Abstract: Exact locations of glacial refugia are relevant for the study of contemporary biodiversity, not only as places less disturbed during the climatic changes but also as sources of rapid expansion of the biota after the Last Glacial cycle. If continuously inhabited over several of the Quaternary glacial cycles, the refugia are readily identifiable by the accumulated genetic diversity. However, the sources of the Holocene range expansion, particularly important for the emergence of present‐day bio‐ and phylogeograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…In contrast to the unlikely northern refugium, we have confidence in the southward expansion inferred for M. incarnatus (Figure 4). Southward expansion has also been previously inferred in C. vindobonensis (Korábek et al, 2020), and our present analysis confirms that this result is robust to latitudinal sampling bias. Although only 12 samples from Bulgaria were included in the earlier analysis compared to 82 used here, the estimated geographic source of the Bulgarian haplotypes remains similar.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to the unlikely northern refugium, we have confidence in the southward expansion inferred for M. incarnatus (Figure 4). Southward expansion has also been previously inferred in C. vindobonensis (Korábek et al, 2020), and our present analysis confirms that this result is robust to latitudinal sampling bias. Although only 12 samples from Bulgaria were included in the earlier analysis compared to 82 used here, the estimated geographic source of the Bulgarian haplotypes remains similar.…”
Section: Discussionsupporting
confidence: 92%
“…For C. vindobonensis and H. thessalica , we base our discussion on the same clades as earlier (Korábek et al, 2020), marked with filled circles in Figure 1. In H. pomatia , haplotypes from clade p‐blue (Figure 1) dominate in the postglacially colonized areas (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The species was actually included in Cepaea until recently, when molecular phylogenetics demonstrated that it is not related to western and central European Cepaea, but to Caucasian Caucasotachea (Korábek et al 2015;Neiber and Hausdorf 2015;Neiber et al 2016). Its natural range extends from the eastern rim of Germany, Poland, and an isolated occurrence in Latvia in the northwest, southwards through the Czech Republic, Austria, and northeastern Italy, across the Balkan Peninsula and southeastern Europe, with isolated occurrences in southern Russia eastwards to the Ural Mountains and from Crimea along the Caucasus to Dagestan (Electronic supplementary material 1; Neiber and Hausdorf 2015;Kajtoch et al 2017;Korábek et al 2020). Caucasotachea vindobonensis becomes adult within two years and copulates in spring and lays 29-67 eggs (mean of 49.3 ± 12.5) in their third year (Staikou 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We constructed a median-joining network (Bandelt et al 1999) based on 292 partial cox1 sequences from the studies of Kajtoch et al (2017) and Korábek et al (2020) using the program PopART (Leigh and Bryant 2015) with e = 0.…”
Section: Sequence Alignment and Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation